Population knowledge, attitudes and practices towards malaria prevention in the locality of Makenene, Centre-Cameroon - Joel Djoufounna; Roland Bamou; Marie Paul Audrey Mayi; Nelly Armanda Kala-Chouakeu; Raymond Tabue; Parfait Awono-Ambene; Dorothy Achu-Fosah; Christophe Antonio-Nkondjio; Timoléon Tchuinkam (Malaria Journal, 2022)
Abstract Background To contribute to the mission of the National Malaria Control Programme (NMCP) and guide future interventions in Cameroon in general, and in Makenene in particular, this study assessed the knowledge, attitudes and practices of the population of Makenene towards the fight against malaria. Methods Using a semi-structured questionnaire, a descriptive cross-sectional household community survey was carried out in randomly selected households in Makenene, a locality situated between forest and savannah ecotypes. Results Out of the 413 households surveyed, all (100%) claimed to have heard of malaria with over 94% (n = 391) associating disease transmission with mosquito bites. The main mosquito control tools used in the area were mosquito nets (92.25%). The majority of participants had good knowledge (55.93%; n = 231), good practices (71.67%, n = 296) but moderate attitudes (47.94%; n = 198) towards malaria control and fight. Good knowledge and practices were recorded mostly in educated persons including public servants and students. Good attitudes were adopted mostly by public servants and students of secondary and higher levels of education. Conclusion In Makenene, the population exhibits good knowledge and practices towards malaria and its control. However, despite high LLINs ownership and use, people still complain about malaria in the area. Control tools should be monitored, repaired or replaced when necessary to support the achievement of the NMCP mission.